Implementation of the Policy Community Based Forest Management (CBFM) Program for the Potorono Forest Sambak Village BKPH Magelang KPH North Kedu Regional Division Central Java - Irfan Budi Santoso; Zainal Hidayat (Journal of Public Policy and Management Review, 2019)
Community Based Forest Management (CBFM) is a cooperative forest management system between the State-Owned Forestry Company (Perum Perhutani) and forest village communities to bring optimal forest resource sustainability. The application of the CBFM program in Central Java is based on the Governor's Decree Number 24 of 2001 concerning Management of Forest Resources among Communities in Central Java and the Perhutani Director’s Decree Number: 682 / Kpts / Dir / 2009 concerning Guidelines for Community Based Forest Management (CBFM). Sambak Village is one of the villages that implemented the CBFM program that is realized through the Wana Hijau Lestari forest village community work program. The aim of this study is to look further at the implementation of the CBFM program in Sambak Village and the factors that affects the implementation of the CBFM in Sambak Village. This study uses a qualitative-descriptive approach with observation, interviews, and documentation as the data collection techniques. The results of this study indicate that the implementation of the CBFM in Sambak Village which is based on the scope of the forest area and the outer forest area, still has several problems. This study found several factors that influence the implementation of the Sambak CBFM associated with human resources such as people who are still not open and the Forest Village Community administrators who are less active, coordination between several parties in CBFM activities still leads to misscommunication, unclear source of funds for implementing CBFM activity and the community environment that are still traditional which create stigma that affects the CBFM implementation. In this study, the author's suggestion is to improve the coordination between the parties involved in CBFM to avoid misscommunication, an integrated marketing system for Wana Hijau Lestari Forest Village Community, Establishment of Village Forest Cooperative (Union), and an expansion in the tourism field.